Elevated plasma Complement Factor H Related 5 Protein is associated with venous thromboembolism - Iglesias Mareque, Maria Jesus; Odeberg, Jacob; Schwenk, Jochen; Trégouët, David Alexandre; Butler, Lynn Marie; Morange, Pierre Emmanuel; Souto, Joan Carles; Soria Fernandez, Jose; Sanchez-Rivera, Laura; Ibrahim-Kosta, Manal; Naudin, Clement; Munsch, Gaëlle; et al. (Royal Institute of Technology, 2023)
The study is based on 6 different cohorts and case control studies of patients with venous thromboembolism (VTE). The six cohorts are briefly as described below:

VEBIOS ER, Swedish acute VTE cohort including 48 cases and 48 controls.

DFW. Swedish acute VTE cohort with 54 cases/146 controls.

FARIVE: French cohort including 582 patients recruited druing initiation of treatment for VTE and 576 hospital-based controls.

VEBIOS Coagulation, Swedish cohort, with 144 cases followed after ending treatment of VTE and 140 controls population-based recluted.

RETROVE, Spanish cohort of 308 cases and 360 controls. Cases were recruted after ending VTE treatment.

MARTHA, French cohort, Patiens with prior VTE. n=774.

The datasets include anonymized participant-level data generated from analyses of plasma samples from the included cohort and case-control studies, including plasma affinity proteomics data, absolute protein quantifications, Thrombin Generation Potential (TGP) measurements, together with clinical chemistry data and clinical information used in the analyses described in the paper.

The data can be made available for validation purposes upon reasonable request (jacob.odeberg@scilifelab.se)

A reasonable request should contain:

1) Name of PI and host organisation

2) Contact details

3) Scientific purpose of data access request

4) Commitment to inform when the data has been used in a publication

5) Commitment not to host or share the data outside the requesting organisation

6) Statement of non-commercial use of data
Keywords: Cardiovascular medicine and haematology not elsewhere classified; Haematology; Medical and Health Sciences; Medicin och hälsovetenskap; Hematology; Hematologi; Cardiology and Cardiovascular Disease; Kardiologi och kardiovaskulära sjukdomar